Multi-Objective in Mapping the Optimal Distributed Generation Configuration through GWOA to Enhance Grid Performance Reliability - Wijaya, I Gede Putu Oka Indra; Ikhsan, Rifki Rahman Nur; Yustika, Lindiasari Martha; Raharjo, Jangkung (Universitas Syiah Kuala, 2025)
In electric power distribution systems, the distance between the load bus and the generating unitsignificantly affects grid efficiency and reliability, with longer distances causing greater voltage drops. To mitigatethis, Distributed Generation (DG) is increasingly being used, generating electricity closer to the point of consumption.Determining the optimal DG location requires advanced metaheuristic methods. This research proposes the Grey WolfOptimizer Algorithm (GWOA) to determine optimal DG placement, tested on the IEEE 14-bus distribution grid. Themethod generated two scenarios: In the first scenario, power losses were reduced by 98.1465% for real power and98.9538% for reactive power compared to the existing conditions, while voltage increased by an average of 0.0127 p.u.for all buses combined. The second scenario also showed a notable voltage increase of 0.0064 p.u. The GWOA methodproves to be an efficient and effective solution for DG placement, enhancing system reliability and protectinghousehold electronic devices.